ACADEMIC WRITING EMPOWERMENT: INTEGRATING DIGITAL LITERACY INTO TEACHING AND LEARNING - Izati, Defi Nor; Hizriani, Nani (Journal of English Educational Study (JEES), 2024)
In an age marked by the pervasive presence of digital technologies, incorporating digital literacy into education has become essential. This study aims to explore the types of digital media utilized by lecturers in teaching and learning Academic Writing, as well as the challenges they encounter. Conducted at Antasari State Islamic University Banjarmasin, the research employs narrative inquiry with interview guidelines. Data gathered from writing instructors, are analysed through narrative analysis. The findings indicate that lecturers utilize diverse digital resources and platforms, such as WhatsApp, Google Site, Microsoft Office, and ChatGPT. However, despite this integration, lecturers encounter challenges in teaching Academic Writing. These challenges encompass students' struggles with standard and scientific English in sources, difficulty in reading and writing English, overreliance on chatbots affecting original writing, student procrastination despite media variety and deadlines, unstable network usage in some areas, and students' reluctance to share thoughts due to fear of making mistakes.Keywords: Digital Literacy; Teaching and Learning; Academic Writing